2002
DOI: 10.2466/pms.2002.94.2.443
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Balance and Jumping Skills in Children with down Syndrome

Abstract: The purpose of this study was to investigate the changes in balance and qualitative and quantitative jumping performances by 20 children with Down syndrome (3 to 6 years) on jumping lessons. 30 typical children ages 3 to 6 years were recruited as a comparison group. Before the jumping lesson, a pretest was given subjects for balance and jumping skill measures based on the Motor Proficiency and Motor Skill Inventory, respectively. Subjects with Down syndrome received 3 sessions on jumping per week for 6 weeks b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 11 publications
2
43
0
2
Order By: Relevance
“…This is a result not only of the difficulty of the requested task, but also due to the patient's inherent inability to comprehend and follow the instructions. Other tests that have been used in people with ID are the functional reach test (Carmeli et al 2005;Hale et al 2007), the single leg stance test (Hale et al 2007;Kokubun et al 1997;Lahtinen et al 2007), the tree-minute walk test (Carmeli et al 2004), and the beam-walking test (Boswell 1991;DePaepe and Ciccaglione 1993;Hale et al 2007;Smith et al 2007;Wang and Ju 2002). Some tests, such as dynamic gait index (Shumway-Cook and Woollacott 2001), the four-step balance scale (Guralnik et al 1994), the tandem stance test (Frzovic et al 1994), or the balance subsection of the Bruininks-Oseretsky Test of Motor Proficiency (Bruininks, 1978) are not applicable in individuals with ID at all (Hale et al 2007).…”
Section: Gait and Balance Assessmentmentioning
confidence: 99%
“…This is a result not only of the difficulty of the requested task, but also due to the patient's inherent inability to comprehend and follow the instructions. Other tests that have been used in people with ID are the functional reach test (Carmeli et al 2005;Hale et al 2007), the single leg stance test (Hale et al 2007;Kokubun et al 1997;Lahtinen et al 2007), the tree-minute walk test (Carmeli et al 2004), and the beam-walking test (Boswell 1991;DePaepe and Ciccaglione 1993;Hale et al 2007;Smith et al 2007;Wang and Ju 2002). Some tests, such as dynamic gait index (Shumway-Cook and Woollacott 2001), the four-step balance scale (Guralnik et al 1994), the tandem stance test (Frzovic et al 1994), or the balance subsection of the Bruininks-Oseretsky Test of Motor Proficiency (Bruininks, 1978) are not applicable in individuals with ID at all (Hale et al 2007).…”
Section: Gait and Balance Assessmentmentioning
confidence: 99%
“…Other common symptoms of depression in DS include sleep and behaviour disturbances, apathy and weight change. Wang et al (2002) also found that DS individuals have a significant delay in motor skills and balance development that persist through adulthood. This has been confirmed by Tsimaras et al (2004) and Angelopoulou et al (1999).…”
Section: B Causes and Characteristics Of Dsmentioning
confidence: 96%
“…Numerous research studies have been performed to determine the aerobic capacity Tsimaras et al, 2003), strength capacity (Shields et al, 2008;Tsimaras et al, 2004), balance and coordination (Carmeli et al, 2002 b ;Wang et al, 2002), and functional capacity (Cowley et al, 2010;Shields et al, 2008) of DS individuals.…”
Section: B Summary Of the Literaturementioning
confidence: 99%
“…DS is the most common of all genetic syndromes 1 and it is caused by chromosomal changes, in this case the trisomy of the 21st chromosome pair, resulting in physical and mental changes 1,2 . This syndrome has been studied by several researchers and, with regard to aspects of child development, they have found that children with DS have a delay in motor skill development, indicating that these skills emerge at a different time compared to children with normal development [3][4][5][6] . Some aspects have been suggested as causes for the delay in the acquisition of motor skills in DS children.…”
Section: Introductionmentioning
confidence: 99%